Sosialiasi Penggunaan Media Gambar pada mata pelajaran PKn Materi Mengenal Makna Lambang Pancasila Siswa kelas IV SDIT Ulumul Qur’an Gebang - Emha Fidiyah Akhadi; Fahrunnisa Fahrunnisa; Rizky Ramadhan (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2023)
The use of image media in Civic Education (PKn) learning, particularly on the topic of understanding the meaning of the Pancasila symbols in fourth-grade elementary school, often faces challenges, especially in enhancing students' comprehension of the abstract concepts involved. This community service program aims to socialize the use of image media as an effective teaching aid in PKn education. The methods employed include training and mentoring teachers in integrating image media into their lessons. The results indicate a significant improvement in students' understanding of the Pancasila symbols and increased motivation to learn. Additionally, the program sparked social change within the school environment, such as new initiatives from teachers to be more creative in using teaching media. This program successfully achieved its goals by fostering positive transformation in the school's learning processes